Small-Scale Analysis of Characteristics of the Wildland–Urban Interface Area of Thessaloniki, Northern Greece - Petros Ganatsas; Nikolaos Oikonomakis; Marianthi Tsakaldimi (Fire, 2022)
In the past few years, the continuous expansion of urban development has created mixed forested, agricultural, and urban areas. These areas are called the wildland–urban interface (WUI), and they are characterized by increased human activities and land-use conversion, and they usually contribute to a high risk of wildfire occurrence. In the case of the peri-urban areas of Thessaloniki city, an effort was made to map, classify, and describe this wildland–urban interface, using Sentinel-2 satellite images of the area and very large scale orthophotos (VLSO) for the human settlements. Object-based image analysis (OBIA) was applied to classify landcover, combined with analysis of field data. The results showed that the WUI area in the city of Thessaloniki appears to the north and east of the city and covers an area of 2203.98 ha. The main characteristics affected by the ecological conditions of this area are the building (or human infrastructure) density, type, and the structure of forest vegetation. Human population pressure was found to be greatly differentiated between WUI areas belonging to different municipalities, the most affected was the municipality of Thessaloniki. A set of fire prevention silvicultural treatments are suggested for mitigating the fire danger in the area, accompanied by appropriate human awareness actions and the involvement of the local society. These measures include the reduction in crown bulk density and increase in crown base height through pruning (at least to 1/3 of total tree height), and low thinning, aiming to ensure that tree crowns of mature Pinus brutia trees are not in contact with one another. Both in the young P. brutia forest and the evergreen vegetation areas, thinning, pruning, and vegetation clearing is recommended adjusted according to each ecosystem.